Saturday

July 26, 2014

July 26, 2014

Posted by **Student** on Tuesday, October 16, 2007 at 5:47pm.

cos(X^2Y^2) = x

I'm really confused what to do now..i think the next steps are:

d/dx [cos(X^2*Y^2)] = d/dx [x]

= -sin(X^2*Y^2)* ((X^2*2Y dy/dx) + (Y^2*2X)) = 1

= -2YX^2 sin(X^2*Y^2) dy/dx + -2XY^2sin(X^2*Y^2) = 1

= -2YX^2 sin(X^2*Y^2) dy/dx = 1 + -2XY^2sin(X^2*Y^2)

= dy/dx = (1 + -2XY^2sin(X^2*Y^2))/ (-2YX^2 sin(X^2*Y^2))

Can someone tell me if this is correct?

**Related Questions**

calc - 1 + x = sin(xy^2) find dy/dx by implicit differentiation 0 + 1 = cos(xy^2...

Math - Calculus - The identity below is significant because it relates 3 ...

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

tigonometry - expres the following as sums and differences of sines or cosines ...

calc.- trig substitution - s- integral s 1/ [ (x^4) sq.rt(x^2+9)] i know x=3tanx...

algebra - Can someone please help me do this problem? That would be great! ...

Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...

Trigonometry - I need to prove that the following is true. Thanks. csc^2(A/2)=...

trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...